THE IMPACT OF PRODUCTIVE ZAKAT EMPOWERMENT IN THE LEVEL OF MUSTAHIK SUCCESS (CASE STUDY OF IZI LAZ SURABAYA) - Andi Asmarani Husein; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research is to serve the information on the role of productive zakat empowerment that affects the success of mustahik efforts by IZI LAZ Surabaya. This research uses the qualitative research method, which is narrative descriptive with a study case research technique. This research object is the alms empowerment program by IZI LAZ Surabaya. It is located in Kalipare village, Malang, Jawa Timur. The result of this research shows that the empowerment by IZI affects mustahik’s development. In the beginning, the mustahik in Kalipare, Malang are lack of employment. With the shuttlecock industry that is empowered by IZI LAZ Surabaya, they managed to lure the people and open new employments for mustahik in Kalipare.Keyword: Empowerment, Productive zakat, MustahikREFFERENCE Suprayitno, Eko. (2005). Ekonomi Islam: Pendekatan ekonomi makro Islam dan konvensional. Yogyakarta: Penerbit Graha Ilmu.Thoriquddin, Moh. (2015). Pengelolaan zakat produktif perspektif maqasid al-syari’ah ibnu ‘asyur. Malang: Penerbit UIN-Maliki Press.Asnaini. (2007). Zakat produktif dalam perspektif hukum Islam. Yogyakarta: Pustaka Belajar.Ansori, Teguh. (2018). Pengelolaan dana zakat produktif untuk pemberdayaan mustahik pada Lazisnu Ponorogo. Muslim Heritage, 3(1), 165-183.  DOI: https://doi.org/10.21154/muslimheritage.v3i1.1274Ahmad., Abdullah. (2014). Metode penelitian ekonomi Islam muamalah. Bandung: Pustaka Setya.A.M. Panjaitan., Jobiliong E., Jony. (2015). Strategi peningkatan jumlah konsumen di rumah makan long’s food. Journal Industrial Services, 1(1), 44-47. DOI: http://dx.doi.org/10.36055/jiss.v1i1.319Wulansari Dwi, Setiawan Hendra. (2014). Analisis peranan dana zakat produktif terhadap perkembangan usaha mikro mustahik (penerima zakat) (studi kasus Rumah Zakat Kota Semarang). Diponegoro Journal of Economics, 3(1): 1-15.Firmansyah. (2013). Zakat sebagai instrumen pengentasan kemiskinan dan kesenjangan pendapatan. Jurnal Ekonomi dan Pembangunan, 21(2), 179-190.Putri PP, Prahesti DD. (2018). Peran dana zakat terhadap peningkatan penghasilan melalui bantuan modal usaha kecil dan mikro. 1, 119-134. DOI: 10.30874/comdev.2017.17Purwanti, Endang. (2012). Pengaruh karakteristik wirausaha, modal usaha, strategi pemasaran terhadap perkembangan UMKM di Desa dayaan dan Kalilondo Salatiga. Among Makarti, 5(9), 13-28.